Tolerability safety and effectiveness of enhanced external counterpulsation versus individual shear rate therapy in patients with lower extremity atherosclerotic disease: A prospective pilot clinical trial. (13th January 2023) - Soubh, Nibras; Hillmeister, Philipp; Buschmann, Eva; Klaproth, Christian; Buschmann, Ivo
Abstract: Aims: We aimed to investigate the tolerability, safety, and effectiveness of enhanced external counterpulsation therapy (EECP) versus individual shear rate therapy (ISRT) in patients with lower extremity atherosclerotic disease (LEAD). Methods: Eighteen patients (age: 73.1 ± 6 years) underwent EECP and ISRT, each daily over five consecutive days in a cross‐over design with a 1 week resting period in between the two regimens. A quality‐of‐life questionnaire was used to assess the therapy experience. Oxygen saturation (SO2 ), relative hemoglobin amount (rHb) and blood flow (Flow) in the capillary‐venous‐system (microcirculation) of the skin were monitored continuously during all therapy sessions using the micro‐lightguide spectrophotometer, also known as oxygen to see (O2C). The effects of EECP and ISRT on the renal function and skeletal muscles were evaluated using serial blood and urine tests. Results: EECP therapy had to be terminated early before the end of the 5th session in 10 patients (55.6%) because of discomfort. Four patients (22.2%) experienced signs of critical limb ischaemia under EECP. The total score of the quality‐of‐life questionnaire was significantly higher (= better tolerated) post‐ISRT compared with EECP. Microcirculation monitoring revealed that ISRT significantly increased the SO2, blood flow and rHb during the therapy. All three parameters remained significantly increased in the observation period after ISRT. The serum levels of creatin kinase and myoglobin increased significantly under EECP. Conclusions: ISRT significantly improves tolerability, safety, and effectiveness over EECP in patients with LEAD.